Upaya Guru Dalam Menumbuhkan Kemandirian Belajar Siswa di SD Negeri 1 Wonoboyo - Setya Permana, Kondang (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2023)
In the context of student autonomous learning, one of the teacher`s efforts is to prioritize autonomy. This research aims to reveal the efforts of 4,444 teachers in encouraging student learning independence at SD Negeri 1 WONOBOYO. Specifically, this research aims to describe teachers' efforts to increase academic independence among students at SD Negeri 1 WONONOYO and students at SD Negeri 1 WONOBOYO. The approach used in this research is qualitative, with a descriptive type of research. Data collection was carried out using observation and interview techniques. Observation techniques are carried out on as many students as possible. To observe the learning independence of students in the upper class, 18 students were randomly selected, and interview techniques were carried out on 9 class teachers in the upper class. All data is then processed through qualitative data analysis steps, namely data reduction, data modeling (data visualization), drawing/verifying argument conclusions and percentages. Based on the results of data analysis, the following research conclusions can be drawn. First, teachers use many teaching methods. Second, teachers foster a sense of enjoyment in learning, including by playing, praising and giving prizes. Three teachers used learning resources using the environment, the internet and teaching materials available at school. The fourth group, totaling 4,444 teachers, promoted learning in the form of lectures, stories and questions and answers.